2005
DOI: 10.1183/09031936.05.00103504
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis treatment outcomes in Europe: a systematic review

Abstract: In order to facilitate the control of tuberculosis (TB), the World Health Organization (WHO) has defined a standardised short-course chemotherapy and a strategy, directly observed therapy. In 2000, WHO surveillance of TB treatments in Europe recorded a successful outcome rate of 77%. The aim of this report is to estimate treatment outcomes in European countries based on published studies and to identify their determinants.A systematic review was conducted of published reports of TB treatment outcomes in Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
46
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 20 publications
14
46
3
3
Order By: Relevance
“…In our study, the overall treatment success rate was 78.2% among a cohort of tuberculosis patients registered for DOTs in Bale Robe Hospital between 2007 to 2012, which is lower than the NTLCP and WHO target of 85%.In our study treatment success rate among all new TB patients was found to be 78.9%. Treatment success rate of 78.2% of the study is in agreement with the previous study conducted in South Ethiopia [9] and much better than that of a study conducted in Gondar which is 29% [15], in Gambella 63.4% [23], and in South Ethiopia 73% [8], low income areas of Italy 56.5% [22] and Europe 74.4% [24]. However, TSR of 78.2% is slightly lower than most studies done in different parts of Ethiopia which is ranging from 80.5% in Gonder [7] to 89.2% in Tigray Region [17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the overall treatment success rate was 78.2% among a cohort of tuberculosis patients registered for DOTs in Bale Robe Hospital between 2007 to 2012, which is lower than the NTLCP and WHO target of 85%.In our study treatment success rate among all new TB patients was found to be 78.9%. Treatment success rate of 78.2% of the study is in agreement with the previous study conducted in South Ethiopia [9] and much better than that of a study conducted in Gondar which is 29% [15], in Gambella 63.4% [23], and in South Ethiopia 73% [8], low income areas of Italy 56.5% [22] and Europe 74.4% [24]. However, TSR of 78.2% is slightly lower than most studies done in different parts of Ethiopia which is ranging from 80.5% in Gonder [7] to 89.2% in Tigray Region [17].…”
Section: Discussionsupporting
confidence: 81%
“…Patients treated by DOTS at the start of therapy had a significantly higher cure rate and decreased tuberculosis-related mortality compared with patients treated by self-administered therapy [5]. The implementation of DOTS and its subsequent surveillance system of treatment outcomes revealed 82% global treatment success rate in DOTs areas in comparison to only 67% in non-DOTs areas [6].…”
Section: Introductionmentioning
confidence: 99%
“…The high default rate documented here is consistent with the high default rates observed in elsewhere in the world (18,(20)(21)(22)(23). In Russia, during the initial year of DOTS implementation, 28% of patient defaulted from treatment (23).…”
Section: Discussionsupporting
confidence: 77%
“…According to data specific to Turkey, the highest rate of death was reported to be seen for the age group >65 (13.4%) (6), while a significant association between death and older age was consistently reported in several studies that may be partly explained by the effect of co-morbidity confounders (8)(9)(10)(11)(12)(13)(14)(15). Given that discontinuation of treatment has also been observed in a number of other conditions that require prolonged drug therapy, such as cardiovascular disease, rheumatic fever, leprosy, epilepsy, diabetes, and malaria prophylaxis, as well as the self-administration of oral contraceptives (16), co-morbidity was associated with a near doubling of the odds for an adverse treatment outcome in our study population.…”
Section: Discussionmentioning
confidence: 99%